DEVELOPING STUDENTS' ECOLOGICAL THINKING THROUGH THE USE OF PHYSICAL SCIENCES IN NATURAL SCIENCE TEACHING (Universal International Scientific Journal, 2026)
The article analyzes the issues of developing students' ecological thinking through the use of physical knowledge in the process of teaching "Natural Sciences" in secondary schools. Methodological approaches aimed at forming students' ecological worldview and responsibility, understanding natural phenomena on a scientific basis, and increasing the effectiveness of education through interdisciplinary connections are considered, and the stages of teaching physical knowledge based on interdisciplinary integration, didactic tasks, and factors for developing ecological thinking are systematically presented. It is shown that interdisciplinary teaching of physical knowledge in natural sciences serves to form and develop ecological thinking and responsibility in students
Keywords: Natural sciences; teaching physical knowledge; ecological thinking